2010
DOI: 10.1111/j.1365-2850.2009.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and recovery as perceived by patients with substance addiction

Abstract: Social relations to therapists and other patients in treatment are important for positive and negative experiences among patients with substance addiction. * Improvements in mental health and substance use were considered as the more important areas of recovery among these patients. * One of the core reasons for premature dropout could be a failure to establish positive social relations and temptations to relapse to substance use. Abstract Research concerning patients with substance addiction and how they perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 37 publications
4
33
0
2
Order By: Relevance
“…However, we found that a significant proportion of patients were not satisfied with ancillary services provided, which suggests that their treatment needs were not met in these areas. In particular, patients were dissatisfied with support provided for housing, financial issues, and employment, which are important in the recovery process (Duffy & Baldwin, 2013;Laudet & White, 2010;Nordfjaern et al, 2010). Reduction or cessation of drug use is the primary outcome of substance abuse treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that a significant proportion of patients were not satisfied with ancillary services provided, which suggests that their treatment needs were not met in these areas. In particular, patients were dissatisfied with support provided for housing, financial issues, and employment, which are important in the recovery process (Duffy & Baldwin, 2013;Laudet & White, 2010;Nordfjaern et al, 2010). Reduction or cessation of drug use is the primary outcome of substance abuse treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients in residential substance abuse treatment have a substantial number of addiction-related problems such as mental disorders (Bergly, Gråwe, & Hagen, 2014;Kessler, 2004;Landheim, Bakken, & Vaglum, 2006) and social problems that may adversely affect their individual functioning. Comprehensive treatment should provide ancillary services related to domains such as housing, financial issues, and employment, as these are all areas of concern for recovery and reintegration into the community (Duffy & Baldwin, 2013;Laudet & White, 2010;Nordfjaern, Rundmo, & Hole, 2010).…”
mentioning
confidence: 99%
“…Dette kan ha forringet kvaliteten på arbeidsallianser mellom pasient og behandlere som er en betydningsfull faktor med hensyn til retensjon (Meier, Barrowclough og Donmall 2005). Oppsummert forskning over tid har påpekt betydningen av relasjon til behandler og sammenheng med utfall av behandling (Meier et al 2005;Kothari, Hardy og Rowse 2010;Nordfjaern, Rundmo og Hole 2010;Brorson et al 2013). …”
Section: Forhold Som Kan Antas å Ha Relevans Til Bruddunclassified
“…In retrospect, the patients´ reoccurring failure to come into sessions in group therapy could have been utilized in relation to self-other treatment objectives and to adaptive and maladaptive shame. Interviews with patients with SUD have revealed that one reason not to re-enter treatment after dropping out relates to feelings of shame (Nordfjaern et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that individuals with SUD themselves rate as most important to successful recovery include decreased substance use, increased ability to regulate emotion, increased positive interpersonal relations, and increased levels of self-esteem (Nordfjaern, Rundmo, & Hole, 2010).…”
Section: Psychotherapy For Sudmentioning
confidence: 99%